J/ψ and D0 production in √sNN = 68.5 GeV PbNe collisions - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (The European physical journal. C, Particles and fields, 2023)
The first measurement of J/ψ and D0 production in PbNe collisions by the LHCb experiment in its fixed-target configuration is reported. The production of J/ψ and D0 mesons is studied with a beam of lead ions with an energy of 2.5 TeV per nucleon colliding on gaseous neon targets at rest, corresponding to a nucleon-nucleon centre-of-mass energy of √sNN = 68.5 GeV. The J/ψ/D0 production cross-section ratio is studied as a function of rapidity, transverse momentum and collision centrality. These data are compared with measurements from pNe collisions at the same energy and show no difference in the observed J/ψ suppression trend when comparing pNe and PbNe peripheral collisions with PbNe central collisions.